Bridging Technology And Financial Competence: A Study On Digital Payment Behavior Among Tourists - Pudin Saepudin; Nenden Dianawati; Endang Komesty Sinaga; Misran (Journal of Tourism Sustainability, 2026)
While digital payment systems have become ubiquitous in tourism, traditional adoption models often overlook the critical role of personal competencies in mature digital ecosystems. This study investigates the impact of self-efficacy and perceived financial literacy (PFL) on digital payment adoption and evaluation among travelers. Using an integrative framework combining TAM, DOI, and UTAUT, and grounded in Social Signaling Theory, data were collected from 495 Indonesian tourists and analyzed via PLS-SEM. The results reveal a significant paradigm shift: traditional drivers such as relative advantage and observability are non-significant, suggesting a "technological domestication" effect where digital benefits have become normalized. Instead, compatibility emerged as the primary driver of actual use. Furthermore, self-efficacy and PFL are core drivers of technological perceptions, with PFL acting as a critical cognitive filter for compatibility and complexity. Finally, actual use strongly predicts user evaluation, confirming Expectation-Confirmation Theory. These findings suggest that in normalized digital landscapes, adoption is driven by contextual resonance and psychological empowerment rather than mere utility. Practically, fintech providers should prioritize user-centric design and literacy-building strategies to foster sustained engagement and long-term loyalty in the travel sector.